Background reduction in long CsI(Tl) crystals - Łukasik J.; Pawłowski P.; Czech B.; Skwirczyńska I.; Brzychczyk J.; Adamczyk M.; Kupny S.; Lasko P.; Sosin Z.; Wieloch A.; Kiš M.; Leifels Y.; et al. (EPJ Web of Conferences, 2015)
A simple method to reduce the background from secondary reactions in telescopes composed of long CsI(Tl) crystals is presented. The method has been developed for the KRATTA [1] modules.